The impact of social capitals on service quality of Chinese educational institutions: A multilevel analysis. (27th June 2017) - Li, Zhichao; Gan, Siyun; Jia, Ru
Summary: Most of the existed researches of educational service quality are concentrated on the definition of service quality in education, measurement methods and the establishment of scales, or on student perception of service quality and its implication, while researches on the causes of educational service quality are quite scarce. In this study, the discussion on the causes of educational service quality was complemented from the perspective of social network, especially through analysis at the team level. A total of 478 copies of social network questionnaires were collected from 15 educational teams. Meanwhile, targeting at the educational institutions' customers, the service quality survey was conducted with 1, 487 copies of valid samples in total. The results indicate that individual‐level social capital in the form of trust relations positively influences educational service quality. Among the group level factors, group centrality and number of cliques have a significant impact on group members' service quality, which also moderate the effect of trust on service quality.